1988
DOI: 10.1148/radiology.167.1.3347723
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of laryngeal cartilage by cancer: comparison of CT and MR imaging.

Abstract: Forty-two patients with laryngeal carcinomas were examined with computed tomography (CT) and magnetic resonance (MR) imaging. The accuracy of both CT and MR imaging in the depiction of cartilage invasion was evaluated in 16 patients by comparing findings at CT and MR with pathologic findings. Calcified cartilage that has been invaded by cancer is frequently seen on CT scans as having an intact contour. Tumor approaching nonossified cartilage may simulate cartilage invasion. On T1-weighted MR images, invaded ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
69
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 0 publications
5
69
1
1
Order By: Relevance
“…In eleven case, on the other hand, there were false positives on the CT. At our study, to accept the positive involvement of cartilage, we use the criterias of extralaryngeal spread, erosion, lysis and sclerosis. In our study based on 28 cases, we found a sensitivity of 89 % and a specificity of 80 %, positive predictive value, 57%; and negative predictive value, 96%.When compared to the studies in the literature our sensitivity values for cartilage invasion are high, while our specificity values were lower (3,15,16,19).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In eleven case, on the other hand, there were false positives on the CT. At our study, to accept the positive involvement of cartilage, we use the criterias of extralaryngeal spread, erosion, lysis and sclerosis. In our study based on 28 cases, we found a sensitivity of 89 % and a specificity of 80 %, positive predictive value, 57%; and negative predictive value, 96%.When compared to the studies in the literature our sensitivity values for cartilage invasion are high, while our specificity values were lower (3,15,16,19).…”
Section: Discussionsupporting
confidence: 45%
“…Several studies in the literature descrıbe that especially in the presence of extralaryngeal spread of tumor, CT can also visualize gross cartilage invasion, and that it not successful in imaging minor cartilage invasion (13,14,15). In the literature sensitivity values of 46-67% and specificity values 87-91% were reported for CT visualization of cartilage retention (3,15,16). Generally the presence of tumor on both sides of the tyhroid cartilage in CT is the only criterion accepted for the verification of neoplastic cartilage invasion (14,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences in Se and Sp, there is no statistical significance between CAT and MRI in cartilage invasion assessment (175). In literature, the pretherapeutic staging accuracy of laryngeal carcinoma has been reported to be 86 and 87.5% with CAT and MRI, respectively (246); moreover, MRI is more sensitive than CAT and presents h a high negative predictive value for detection of neoplastic cartilage invasion (177,215).…”
mentioning
confidence: 99%
“…These are the areas in which cross-sectional imaging plays a major role in identifying the tumor spread, which may not be readily accessed by laryngoscope or mirror examinations. [13][14][15] Coronal and sagittal reformatted images provide an accurate and reliable assessment of craniocaudal extension of disease, which is often limited by the axial image acquisition only, even with additional maneuvers. In the era of isovoxel multidetector CT technology, the staging of laryngeal cancer should be performed with contrastenhanced neck CT with thin-section coronal and sagittal reformation.…”
Section: Discussionmentioning
confidence: 99%